Arterial desaturation due to pulmonary arteriovenous malformations after the Kawashima Operation - Rohit S Loomba (Wolters Kluwer Medknow Publications, 2016)
Arterial desaturation may occur after the Kawashima procedure and, in the absence of venovenous collaterals is usually due to pulmonary arteriovenous malformations. Stenting of the pulmonary arteries, oxygen therapy, and pulmonary vasodilators such as sildenafil have not been able to resolve the arterial desaturation and the only way to do this has been Fontan completion. The time course of the formation of these malformations after the Kawashima and the progression of cyanosis and its resolution after the Fontan has only been demonstrated in case reports and small case series. We pool the available data to model arterial saturations in patients with pulmonary arteriovenous malformations after the Kawashima procedure.